Narcotics Crime as A Phenomenon of Transnational Organized Crime - Zainab Ompu Jainah (International Conference On Law, Business and Governance (ICon-LBG), 2013)
Illicit drug trafficking undermine governance, institutions and societal cohesion. Drug traffickers typicallyseek the path where the rule of law is weak. In turn, drug-related crime deepens vulnerability to instabilityand poverty. In the period of the past two decades, Indonesia has become one of the countries that servemajor markets from narcotics syndicate of international dimension for commercial purposes. For drugtrafficking network in Asian countries, Indonesia is considered as the market (market-state) is the mostprospective commercial for the International syndicates operating in developing countries